PENGARUH GERAKAN GREEN SCHOOL TERHADAP KESADARAN LINGKUNGAN PESERTA DIDIK DI SMA NEGERI 4 PEKANBARU - Novita Putri Ariska; Sri Erlinda; Supentri Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This research background in the foreground with the school environment becomes a green school. Green school green schools, namely, but not just the physical appearance of a lush green or school, but the school has exist programmes and activities of education leads to awareness and environmental wisdom. Environmental awareness is the ability of a person to be aware of the relationship between human activity with the State of the surrounding environment to create a safe and healthy environment. Formulation of the problem in this research is whether there is influence of green school movement towards environmental awareness of students in SMA Negeri 4 Pekanbaru. The purpose of this research is to know the pelaksananan, practice and influence of green school terhdap environmental awareness in SMA Negeri 4 Pekanbaru. As for that being a sample is the learners with a total 92 people. The technique of data collection was done via the question form, interview and documentation. The results of this research show that the implementation of green school namely amounted to 83.38%. Practice environmental awareness i.e. of 76.46%, and there was significant influence between the go green towards environmental awareness in SMA Negeri 4 Pekanbaru, this is evidenced by a series of simple linear regression test between against the variable X the variable Y, retrieved Fhitung 21.940 Ftabel 3.95 with N = 92, meaning there is influence significant between learning green school towards environmental awareness.Keywords: Green School, Environmental awareness